2008
DOI: 10.1128/iai.01386-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carbon Nutrition for Pathogenic and Commensal Escherichia coli Strains in the Mouse Intestine

Abstract: The carbon sources that support the growth of pathogenic Escherichia coli O157:H7 in the mammalian intestine have not previously been investigated. In vivo, the pathogenic E. coli EDL933 grows primarily as single cells dispersed within the mucus layer that overlies the mouse cecal epithelium. We therefore compared the pathogenic strain and the commensal E. coli strain MG1655 modes of metabolism in vitro, using a mixture of the sugars known to be present in cecal mucus, and found that the two strains used the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
434
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(446 citation statements)
references
References 50 publications
10
434
1
1
Order By: Relevance
“…For example, an E. coli mutant deficient in the catabolic pathway for L-fucose demonstrated a marked decrease in colonization of the rectal mucus (Snider et al, 2009). Similar results were observed in mice and in vitro with E. coli MG1655 Fabich et al, 2008). Fucose is only a minor component of calf ileal mucus (Montagne et al, 2000), and thus was not evaluated in this study.…”
Section: Discussionsupporting
confidence: 57%
“…For example, an E. coli mutant deficient in the catabolic pathway for L-fucose demonstrated a marked decrease in colonization of the rectal mucus (Snider et al, 2009). Similar results were observed in mice and in vitro with E. coli MG1655 Fabich et al, 2008). Fucose is only a minor component of calf ileal mucus (Montagne et al, 2000), and thus was not evaluated in this study.…”
Section: Discussionsupporting
confidence: 57%
“…Although no direct relation between the CreBC of microbes and the metabolism within the gastrointestinal tract has been reported, previous studies have demonstrated that CreBC responds to the change of the carbon sources that are utilized by microbes (39). Various types of microbes colonize the human intestine to compete for carbon resources (46). Thus, we proposed that the CreBC system may be important for microbes to utilize the frequently changing carbon sources.…”
Section: Fig 5 the Kinase Assaysmentioning
confidence: 94%
“…This sharing of resources is referred to as 'resource partitioning'. Pathogenic and commensal strains of Escherichia coli were shown, in a series of in vitro and in vivo experiments conducted by Fabich et al (2008) to share carbohydrate resources in gut mucus. Although both strains of E. coli utilised arabinose, fucose and N-acetylglucosamine for growth, the pathogenic strain also used galactose, hexuronates, mannose and ribose.…”
Section: Discussionmentioning
confidence: 99%